Study of the Effect of Compensation Device with 6% Reactance Rate on 4 th Harmonic Amplification - PAN Caimin (Kongzhi Yu Xinxi Jishu)
Based on the analysis of the conditions for the existence of even harmonics and the series and parallel resonant points of common reactance rate for reactive power compensation, and combining with the comparison of measured data and simulation analysis, it studied the principle of 4th harmonic amplification when the compensation device with 6% reactance rate was turned on step by step, and proposed schemes to avoid it.